Fretting Wear Characteristics of SLM-Formed 316L Stainless Steel in Seawater - Mingji Huang; Ping Chen; Xiaoxi Qiao (Lubricants, 2022)
The fretting wear characteristics of two different energy density 316L stainless steels formed by selective laser melting (SLM) under different friction conditions are studied. The image method was used to study the porosity of two samples with different energy densities (46.88 J/mm3, 98.96 J/mm3) formed by SLM. The dynamic wear test, respectively, evaluates its wear morphology and wear depth under three conditions: dry friction, distilled water, and an 3.5% NaCl solution. The porosity of the samples with SLM forming an energy density of 46.88 J/<semantics>mm3</semantics> and 98.96 J/<semantics>mm3</semantics> are 7.66% and 1.00%, respectively. Under the three conditions, the friction coefficient and wear depth of the samples with high energy density are smaller than those of the samples with low energy density; the friction of the samples with two energy densities in aqueous solution is faster than dry friction in air and tends to be stable. The friction coefficient in 3.5% NaCl solution is the smallest; when the energy density is constant, the wear depth of the fretting wear is the largest under dry friction and the smallest in distilled water. Under dry-friction conditions, the wear mechanisms of fretting wear are mainly oxidative wear and adhesive wear. In the fretting wear in the distilled water and the 3.5% NaCl solution, both wear mechanisms are abrasive wear and fatigue wear.